The clinicopathological and gene expression patterns associated with ulceration of primary melanoma. (1st October 2014) - Jewell, Rosalyn; Elliott, Faye; Laye, Jonathan; Nsengimana, Jérémie; Davies, John; Walker, Christy; Conway, Caroline; Mitra, Angana; Harland, Mark; Cook, Martin G.; Boon, Andy; Storr, Sarah; et al.
Summary: Ulceration of primary melanomas is associated with poor prognosis yet is reported to predict benefit from adjuvant interferon. To better understand the biological processes involved, clinicopathological factors associated with ulceration were determined in 1804 patients. From this cohort, 348 primary tumor blocks were sampled to generate gene expression data using a 502‐gene cancer panel and 195 blocks were used for immunohistochemistry to detect macrophage infiltration and vessel density. Gene expression results were validated using a whole genome array in two independent sample sets. Ulceration of primary melanomas was associated with more proliferative tumors, tumor vessel invasion, and increased microvessel density. Infiltration of tumors with greater number of macrophages and gene expression pathways associated with wound healing and up‐regulation of pro‐inflammatory cytokines suggests that ulceration is associated with tumor‐related inflammation. The relative benefit from interferon reported in patients with ulcerated tumors may reflect modification of signaling pathways involved in inflammation.